PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI - Martha, Ade Rio; Rahardjo, Kusdi; Prasetya, Arik (FIA UB, 2020)
This research was conducted to determine the effect of transformational leadership style on performance of employee mediated by work motivation variables. This type of reseaarch is explanatory with a quantitaiive approach. The data used were primary data that obtained and collected through direct survey using questionnaires to respondents. Proportional random sampling method was used in this research. The participants were 109 employees of PT. Gersindo Minang Plantation-Palm Oil Mill (GMP-POM). Explanatory methods and Structural Equation Modeling (SEM) were used to explain between variables. In analyzing the data, this research evaluated the measurementt model (Outer model), structuraal model (Inner model), goodness of fit, and hypotheses tested using Bootstrapping. The results of this research indicated that the transformational leadership style has a significant positiive effect on work motivation. The transformatiional leadershiip style has a posiitive and not signifiicant effect on employee performaance, meanwhile, work motivatiion has a significant positiive effect on employee performaance. This research also proved that work motivatiion successfully mediated the effect of transformational leadership styles on employee performaance from insignificant positive to significant positive.